"Il lato oscuro della valutazione": The perception of evaluation and assessment in a University context - Antonella Nuzzaci; Anna Salerni; Maria Vittoria Isidori; Alessandro Vaccarelli (Pensa MultiMedia, 2018)
The aim of this contribution is to focus on the reasons for the rejection of evaluation practices in the field of higher education and to understand how this refusal is connected to the "mechanism of unveiling of the educational system" that the evaluation implements. It attempts to provide an interpretative framework regarding the perception of students (but also university professors) of evaluation practices adopted in the university context, proposing to give an explanation that, although provisional, can contribute to the understanding of the refusal that usually accompanies the evaluation, which becomes not only the spy of a malaise but also that of a malfunctioning of teaching. This perception is an intervening factor, often neglected, but important if we want to fully understand the "how, when and why" the learning and the meaning of teaching are realized, and if we want to reveal the reasoning behind the educational action system with which it is possible to clarify the logics that guide the management of the interventions by the teachers.